SYMBOLISM OF ANIMALS AS OBJECTS OF HUNTING IN TRADITIONAL CULTURE (ON MATERIAL OF THE YAKUT LANGUAGE) - Petrovna Pavlova, Irina (Revista Inclusiones, 2020)
The article deals with hunting terms in the Yakut language that name the objects of hunting (moose, ermine, sable, hare). The semantics of the nominations encompass a wide cultural and ethnographic background and are confirmed by the facts of mythological (folk) conceptions. The existence of the special taboo language of hunters is illustrated by a number of vivid examples. The conclusion is made about the close connection between language phenomena and the culture of a people.